Johnstone's Levels of Representation in Science Learning - Anggit Grahito Wicaksono (Program Studi Pendidikan Fisika, FITK, UNSIQ, 2022)
Science education, beginning in elementary and junior high schools, should be able to meet the demand for grasping the notion of science. Junior high school science learning is an integrated science learning that comprises three branches, namely biology, physics, and chemistry. Understanding chemistry as a whole, which comprises three levels of representation, namely macroscopic, submicroscopic, and symbolic, is what learning chemistry entails. The purpose of this article is to review the literature on the three levels of representation theory and the relationship between the three levels of representation in learning. Johnstone's levels of representation have an impact on science learning by encouraging integration across multiple representation. This qualitative research is library research with books and other literature as the main object, such as scientific journals and scientific articles. The term represents has several meanings, including to symbolize, to recall thoughts through images or imagination, and to provide a depiction. Levels of representation refer to the use of three levels of representation to represent a phenomenon. The three levels of representation, namely the macroscopic, submicroscopic, and symbolic levels, are interconnected and contribute to students' ability to understand and comprehend abstract chemistry.